Nursing Cares in tissue plastiminogen activator therapy - Sh. S Bassampoor (Tehran University of Medical Sciences, 2002)
The main therapeutic objective of emergency after acute myocardial infarction (MI) is limiting the infarcted area through the opening of occluded artery, decreasing demand of myocardial oxygen and preventing MI complications.When arterial wall is injured, the collagen tissue is exposed to platelet aggregation that leads to releasing adenosine 5 diphosphate and subsequent to it, platelet adhesion and formation of fibrin is occured. After a while fibrin activates directly the fibrinolytic system, then plasminogen activator is infused and it changes plasminogen into plasmin so that it makes fibrin to be digested.TPA is one of the most effective thromboclastic drugs. It is an enzyme that is produced through recombinant DNA. TPA is a type of fibrin that is infused in circulatory system and binds to fibrin in a thrombus and it converts the plasminogen to plasmin. It is prescribed for adults presenting the early signs of acute myocardial infarction.The recommended dose of TPA for the adults weighing more then 65 Kg is 100 mg. If the patient weighs less than 65 Kg, dosage is determined by a formula as the following: 1.25 mg TPA per Kg body weight.The primary period of prescribing TPA in patients suffering from MI is at the time of transferring them to the hospital or emergency ward. More over, treatment is carried on with effective dose of TPA for 3 hours.The fundamental nursing procedures for the patients receiving TPA consist of complete assessing the patient and obtaining basic information and history of the patient's health and disease.During the infusion of TPA, the patient's bleeding should be continually checked. The recovery signs after TPA infusion is indicated as dysrhythmia, due to reperfusion and it should not be taken into consideration as a negative sign. Some other recovery signs are relieving chest pain and reversing ST segment